Factors associated with dietary and fluid restriction adherence of chronic kidney disease patients undergoing hemodialysis - Safitri, Dewin; Pahria, Tuti; Rahayu, Urip (Media Keperawatan Indonesia, 2023)
Non-adherence of hemodialysis patients to diet and restriction of fluid restriction has a negative impact on health status. Various factors are associated with non-adherence to dietary and fluid restriction in chronic kidney disease patients undergoing hemodialysis including patient characteristics such as age, gender, education, occupation, length of time undergoing hemodialysis, self-efficacy, motivation and social support. This study aims to analyze the most dominant factors associated with dietary compliance and fluid restriction in chronic kidney disease patients undergoing hemodialysis. This study used a descriptive correlational design with a cross-sectional approach. The sample in this study were patients with chronic kidney disease who underwent hemodialysis as many as 80 respondents. Collecting data using the respondent characteristic questionnaire, General Self-Efficacy Scale, Treatment of Motivation Questionnaire, Multidimensional Scale of Perceived Social Support dan Dialysis Diet and Fluid Nonadherence Questionnaire. Data were analyzed using multiple linear regression. The result of the correlation analysis showed that there was no relationship between gender, education and occupation with dietary compliance and fluid restriction (p > .005). Factors related to dietary compliance and fluid restriction were age, length of hemodialysis, self-efficacy, motivation and social support (p < .005). multivariate analysis using multiple linear regression tests showed that the most dominant factor associated with dietary compliance and fluid restriction was self-efficacy (R2 = .504, p = .000). Thus, it is important to periodically assess the patient's self-efficacy and plan actions to increase self-efficacy so that adherence to diet and fluid restriction can also be improved.